Interaction behavior between bisphenol AP and pepsin: Insights from density functional theory, and spectroscopic and molecular dynamic simulation - Guan, Tianzhu; Li, Ning; Gao, Ya; Zhang, Longfei; Hu, Qin; Li, Huaxiang; Yang, Ming; Xiao, Lixia; Yuan, Lei; Yang, Zhenquan (Quality assurance and safety of crops & food, 2022)
Overuse of polymer materials has caused increasing direct human exposure to bisphenol AP (BPAP). Through the contaminated environment and food chains, the adverse effects of BPAP on humans and plants induce growing concerns. In this study, the effects of BPAP on pepsin structure changes were exhaustively investigated by multi-spectral methods. Under mimic physiological conditions, BPAP caused a gradient intrinsic fluorescence quenching by inducing microenvironmental changes surrounding residues with the endogenous fluorescence in pepsin. During the ground-state complex formation, the senior structures of pepsin were altered by BPAP addition. Fourier transform infrared spectroscopy and circular dichroism spectroscopy showed that the secondary and tertiary structures of pepsin were changed after the addition of BPAP. Thermodynamic parameter analysis demonstrated that the pepsin and BPAP binding was a spontaneous process that was mainly driven by hydrophobic interaction and van der Waals force. With BPAP as the subject of density functional theory experiments, the energies of the highest occupied molecular orbital, the lowest unoccupied molecular orbital, and the electrostatic potential were calculated to evaluate the electronic distribution of BPAP. Molecular docking experiments displayed that in the specific interaction pattern, hydrogen-bonding between one of the hydroxyl groups and specific amino acids was vital in stabilizing the BPAP−pepsin complex. The root mean square deviation, total hydrogen bonds statistic, and Ramachandran map obtained by molecular dynamic simulations validated the findings and predicted the rationality of the complex structure. This study provides an experimental and theoretical basis for understanding the binding mechanism of bisphenol pollution and pepsin. It also puts forward strategies to strengthen food safety and achieve precise control of environmental contaminants in the food industry.